Nicotine vaccines for smoking cessation - Hartmann-Boyce, Jamie; Cahill, Kate; Hatsukami, Dorothy; Cornuz, Jacques (Cochrane database of systematic reviews, 2012)
By reducing the amount of nicotine that reaches the brain when a person smokes a cigarette, nicotine vaccines may help people to stop smoking or to prevent recent quitters from relapsing. The aims of this review are to assess the efficacy of nicotine vaccines for smoking cessation and for relapse prevention, and to assess the frequency and type of adverse events associated with the use of nicotine vaccines. We searched the Cochrane Tobacco Addiction Review Group specialised register for trials, using the term 'vaccine' in the title or abstract, or in a keyword (date of most recent search April 2012). To identify any other material including reviews and papers potentially relevant to the background or discussion sections, we also searched MEDLINE, EMBASE, and PsycINFO, combining terms for nicotine vaccines with terms for smoking and tobacco use, without design limits or limits for human subjects. We searched the Annual Meeting abstracts of the Society for Research on Nicotine and Tobacco up to 2012, using the search string 'vaccin'. We searched Google Scholar for 'nicotine vaccine'. We also searched company websites and Google for information related to specific vaccines. We searched clinicaltrials.gov in March 2012 for 'nicotine vaccine' and for the trade names of known vaccine candidates. We included randomized controlled trials of nicotine vaccines, at Phase II and Phase III trial stage and beyond, in adult smokers or recent ex-smokers. We included studies of nicotine vaccines used as part of smoking cessation or relapse prevention interventions. We extracted data on the type of participants, the dose and duration of treatment, the outcome measures, the randomization procedure, concealment of allocation, blinding of participants and personnel, reporting of outcomes, and completeness of follow-up.Our primary outcome measure was a minimum of six months abstinence from smoking. We used the most rigorous definition of abstinence, and preferred cessation rates at 12 months and biochemically validated rates where available. We have used the risk ratio (RR) to summarize individual trial outcomes. We have not pooled the current group of included studies as they cover different vaccines and variable regimens. There are no nicotine vaccines currently licensed for public use, but there are a number in development. We found four trials which met our inclusion criteria, three comparing NicVAX to placebo and one comparing NIC002 (formerly NicQbeta) to placebo. All were smoking cessation trials conducted by pharmaceutical companies as part of the drug development process, and all trials were judged to be at high or unclear risk of bias in at least one domain. Overall, 2642 smokers participated in the included studies in this review. None of the four included studies detected a statistically significant difference in long-term cessation between participants receiving vaccine and those receiving placebo. The RR for 12 month cessation in active and placebo groups was 1.35 (95% Confidence Interval (CI) 0.82 to 2.22) in the trial of NIC002 and 1.74 (95% CI 0.73 to 4.18) in one NicVAX trial. Two Phase III NicVAX trials, for which full results were not available, reported similar quit rates of approximately 11% in both groups. In the two studies with full results available, post hoc analyses detected higher cessation rates in participants with higher levels of nicotine antibodies, but these findings are not readily generalisable. The two studies with full results showed nicotine vaccines to be well tolerated, with the majority of adverse events classified as mild or moderate. In the study of NIC002, participants receiving the vaccine were more likely to report mild to moderate adverse events, most commonly flu-like symptoms, whereas in the study of NicVAX there was no significant difference between the two arms. Information on adverse events was not available for the large Phase III trials of NicVAX.Vaccine candidates are likely to undergo significant changes before becoming available to the general public, and those included in this review may not be the first to reach market; this limits the external validity of the results reported in this review in terms of both effectiveness and tolerability. There is currently no evidence that nicotine vaccines enhance long-term smoking cessation. Rates of serious adverse events recorded in the two trials with full data available were low, and the majority of adverse events reported were at mild to moderate levels. The evidence available suggests nicotine vaccines do not induce compensatory smoking or affect withdrawal symptoms. No nicotine vaccines are currently licensed for use in any country but a number are under development.Further trials of nicotine vaccines are needed, comparing vaccines with placebo for smoking cessation. Further trials are also needed to explore the potential of nicotine vaccines to prevent relapse. Results from past, current and future research should be reported in full. Adverse events and serious adverse events should continue to be carefully monitored and thoroughly reported.